A Helping Hand or the Long Arm of the Law? : Do Carrots or Sticks Work Best for Bringing Informal Firms into the Formal Sector? - de Andrade, Gustavo Henrique (World Bank, Washington, DC, 2015)
Since 2004, 75 percent of countries have adopted at least one reform making it easier to register a business. Yet, despite these efforts, the majority of firms in most developing countries remain informal. This is of concern to policymakers, who worry that a large stock of informal firms results in a loss in tax revenue, unfair competition for formal firms, and a culture of informality. Much less attention has been given to increasing the costs of remaining informal through better enforcement of existing laws. A field experiment conducted with the State Government of Minas Gerais in the city of Belo Horizonte in Brazil provides an opportunity to test the relative merits of further cost-reduction versus enforcement in formalizing firms. Further experimentation as to how to better improve the process of enforcement of regulations, seems an important area for policy and research efforts going forward.